Binding of Macrophage Receptor MARCO, LDL, and LDLR to Disease-Associated Crystalline Structures - Alberts, Anika; Klingberg, Annika; Hoffmeister, Leonie; Wessig, Anne Kathrin; Brand, Korbinian; Pich, Andreas; Neumann, Konstantin (Frontiers in Immunology, 2020)
Endogenous and exogenous crystalline structures are involved in various pathologies and diseases in humans by inducing sterile inflammation, mechanical stress, or obstruction of excretory organs. The best studied of these diseases is gout, in which crystallization of uric acid in the form of monosodium urate (MSU) mainly in synovial fluid of the joints leads to sterile inflammation. Though some of these diseases have been described for centuries, little is known about if and how the immune system recognizes the associated crystals. Thus, in this study we aimed at identifying possible recognition molecules of MSU using liquid chromatography-mass spectrometry (LC MS) analysis of MSU-binding serum proteins. Among the strongest binding proteins, we unexpectedly found two transmembrane receptors, namely macrophage receptor with collagenous structure (MARCO) and low-density lipoprotein (LDL) receptor (LDLR). We show that recombinant versions of both human and mouse MARCO directly bind to unopsonized MSU and several other disease-associated crystals. Recombinant LDLR binds many types of crystals mainly when opsonized with serum proteins. We show that this interaction is predominantly mediated by LDL, which we found to bind to all crystalline structures tested except for cholesterol crystals. However, murine macrophages lacking LDLR expression do neither show altered phagocytosis nor IL-1ß production in response to opsonized crystals. Binding of LDL to MSU has previously been shown to inhibit the production of reactive oxygen species (ROS) by human neutrophils. We extend these findings and show that LDL inhibits neutrophil ROS production in response to all most crystals tested, even cholesterol crystals. The inhibition of neutrophil ROS production only partly correlated with the inhibition of IL-1 production by peripheral blood mononuclear cells (PBMCs): LDL inhibited IL-1ß production in response to large MSU crystals, but not small MSU or silica crystals. This may suggests distinct upstream signals for IL-1ß production depending on the size or the shape of the crystals. Together, we identify MARCO and LDLR as potential crystal recognition receptors, and show that LDL binding to diverse disease-associated crystalline structures has variable effects on crystal-induced innate immune cell activation.